J-shaped association between serum albumin levels and long-term mortality of cardiovascular disease: Experience in National Health and Nutrition Examination Survey (2011–2014) - Li, Xu; Zhang, Yue; He, Yi; Li, Ke-Xin; Xu, Ruo-Nan; Wang, Heng; Jiang, Ting-Bo; Chen, Wei-Xiang; He, Yong-Ming (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiovascular disease (CVD) is a constellation of heart, brain, and peripheral vascular diseases with common soil hypothesis of etiology, and its subtypes have been well-established in terms of the albumin-mortality association. However, little is known regarding the association between albumin and CVD mortality, especially the nonlinear association. We aimed to investigate the association of albumin levels with long-term mortality of CVD. Methods: This study included all CVD patients who participated in the National Health and Nutrition Examination Survey (NHANES 2011-2014). CVD was defined as coronary heart disease, stroke, heart failure, or any combination of these 2 or 3 diseases. Serum albumin was tertile partitioned: tertile 1, <4.1; tertile 2, 4.1-4.3; and tertile 3, >4.3 g/dL. COX proportional hazards model was used to assess the association between the serum albumin levels and CVD mortality. Restricted cubic spline (RCS) curves were used to explore the non-linear relationship. Results: A total of 1070 patients with CVD were included in the analysis, of which 156 deaths occurred during a median 34 months of follow-up. On a continuous scale, per 1 g/dL decrease was associated with an adjusted HR (95%CI) of 3.85(2.38-6.25). On a categorical scale, as compared with tertile 3, the multivariable adjusted hazard ratio (95%CI) was 1.42(0.74-2.71) for the tertile 2, and 2.24(1.20-4.16) for the tertile 1, respectively, with respect to higher mortality. RCS curve analysis revealed a J-shaped association between albumin and CVD mortality. In conclusions: A J-shaped association between low serum albumin levels and increased long-term mortality of CVD has been revealed. This J-shaped association’s implications for CVD prevention and treatment are deserving of being further studied.